THE EFFECT OF REGIONAL ORIGINAL REVENUE AND GENERAL ALLOCATION FUND ON CAPITAL EXPENDITURE IN WEST JAVA PROVINCE FOR THE 2017-2020 PERIOD - Saska Salsadilla Kurniawan; Sendi Gusnandar Arnan (Jurnal Ekonomi, 2023)
At present, the existence of regional autonomy is intended to be the authority of government affairs to allocate its sources of income in order to accelerate the development of a prosperous society through services and empowerment. This study aims to determine how much influence government revenue sources, namely Regional Original Revenue and General Allocation Fund on Capital Expenditure of West Javan cities in 2017-2020. In the research conducted, the authors analyzed the data with descriptive quantitative methods, namely by drawing and analyzing data based on existing facts and information. The research data used is secondary data, consisting of data on Regional Original Revenue, General Allocation Fund, and Capital Expenditure which comes from the budget realization report at the Bandung City Regional Financial and Asset Management Agency for the 2017-2020 period. The SPSS statistic 23 software was used as a data processing tool along with the classical assumption test and multiple linear regression as the data analysis method in this study. The result of the study prove that Regional Original Revenue has a significant affect on Capital Expenditure while the General Allocation Fund has no significant affect on Capital Expenditure. The magnitude of the influence of regional original revenue and general allocation fund contributed 73,8% to capital expenditure. This means that the more revenue realization obtained by the local government from PAD and DAU, the more funds can be channeled to its capital expenditure budget.